PRODUK KEGIATAN USAHA PERBANKAN SYARIAH DALAM MENGEMBANGKAN UMKM DI ERA MASYARAKAT EKONOMI ASEAN (MEA) - Santoso Santoso; Ulfah Rahmawati (LP2M IAIN kUDUS, 2016)
Economic life is at frst simple. Activities of production, consumptionand distribution is very simple. Along with the times, humanpopulation increased so that the economic activities also increased.One of government efforts to welcome the Syariah EconomicCommunity and improve the performance of Micro, Small andMedium Enterprises is their growth of conducive business climateconducted by the central government and local governments toestablish legislation and policy. The problem often faced by eachUMKM is not apart from the need for funds to fnance their business.To meet their needs, almost all UMKM utilized banking like theIslamic bank. Islamic bank is a fnancial institution that servesas an intermediary for the excess funds to parties who lack fundsfor operations and other activities in accordance with Islamic lawthat funds in the form of fnancing, such as mudaraba fnancing,Musharaka fnancing and murabaha fnancing. Financing hasbeen distributed by Islamic banks to contain the risk of congestioncallable, so it can affects the bottom line.